Improving Affordability and Equity in Medicare Advantage - Zirui Song MD, PhD; Sanjay Basu MD, PhD (SAGE Publishing, 2019)
Facing projected growth in federal deficits, policymakers may increasingly look to Medicare for opportunities to slow spending. Medicare Advantage, which has grown to over one-third of the Medicare population, now costs the federal government over $230 billion a year. Competition in the program is weak in many parts of the country and federal subsidies are distributed unevenly to beneficiaries who are enrolled. This article offers a potential approach toward reforming the Medicare Advantage payment system, which could lower federal costs and enhance equity in the program. It builds a simple framework containing policy options and uses 2015 Centers for Medicare and Medicaid Services data to estimate the stylized impact on federal spending and enrollee benefits.